2000
DOI: 10.1046/j.1365-294x.2000.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and natural selection in the Tenerife gecko Tarentola delalandii: testing historical and adaptive hypotheses

Abstract: Combining phylogeographic and matrix correspondence approaches in the analysis of geographical variation provides a fruitful approach to inferring the causes of molecular and morphological evolution within species. Here we present a study on the gecko Tarentola delalandii on the island of Tenerife, Canary Islands, which provides an outstanding model of an exceptionally high degree of phylogeographic differentiation in magnitude and pattern on a small spatial scale. We reconstruct the population history of T. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 74 publications
4
95
0
Order By: Relevance
“…2015), and also in studies of mitochondrial haplotype diversity in several animal groups (e.g., Gübitz et al. 2000; Brown et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2015), and also in studies of mitochondrial haplotype diversity in several animal groups (e.g., Gübitz et al. 2000; Brown et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It had been suggested that this difference stems from habitat discontinuities between and within paleo‐islands that causes strong divergent selection and impedes migration (Gübitz et al. 2000; Moya et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations